SOCIAL STRUCTURE AND GROWTH RATE OF THE ARGENTINE-ANT Linepithema humile (Mayr, 1868) - Diehl-Fleig, Eduardo; Berti Filho, Evoneo; Bueno, Odair Correa; Diehl, Elena (REVISTA DE AGRICULTURA, 2017)
This work evaluated the agonistic behavior among workers of different nests of the Argentine-ant Linepithema humile, the period of sexual production, the sexual proportion, the variation of intranest population in the summer and in the winter, and. tThe growth rate of little colonies of 25 nests in Limeira, SP., were determined by Tthe intranest population were determined by counting the individuals of ten nests, and the growth rate to dissemination with 10, 50, 100, 150, 200, and 500 workers. The Limeira population presented unicolonial social structure with no agonistic Â behavior among different nests. The sexual production was in the summer, with female-biased sexual investment (2.4 : 1). The size of the disseminated had a positive influence on the production of total offspring, but it was negative regarding the per capita production.